Gas exchange characteristics of the hybrid Azadirachta indica × Melia azedarach - Cheng X (iForest - Biogeosciences and Forestry, 2015)
The hybrid Azadirachta indica × Melia azedarach is a new plant variety that was obtained through somatic hybridization. The plant could grow normally in regions with an average annual temperature of 15 °C, and it had a higher concentration of active insecticidal substance in its seeds. Therefore, the hybrid will likely become a valuable new tree species in subtropical and warm temperate regions. However, the photosynthetic physiological characteristics of A. indica × M. azedarach remain unknown. The photosynthetic gas exchange of the hybrid at three different ages (one year old (AM1), three years old (AM3), and five years old (AM5)) were measured. The specific leaf mass per area (LMA), leaf N, leaf P, and leaf N/P of each tree sample were measured, and the photosynthetic N and P use efficiencies (PNUE and PPUE, respectively) were also calculated. The maximum leaf net photosynthetic rate Pa (based on area), Pm (based on mass), light saturation point (LSP), light compensation point (LCP), stomatal conductance (gs), and transpiration rate (Tr) of A. indica × M. azedarach decreased with increasing tree age, whereas the instantaneous water use efficiency (WUE) increased with age. The photosynthetic capacity showed no significant differences between AM3 and AM5 but was significantly higher in AM3 and AM5 when compared with AM1.The Pa, Pm, apparent quantum yield (AQY), LSP, gs, and Tr of A. indica × M. azedarach were significantly lower than that of the parental M. azedarach, whereas the dark respiration rate (Rd) and WUE were significantly higher than that of M. azedarach. A reduction in the maximal photosynthetic rate of A. indica × M. azedarach that was observed with increased age was primarily related to the increased LMA and the decline in leaf nitrogen (N) and leaf phosphorus (P) concentrations. Additionally, the decline in stomatal conductance (gs) was also an important factor leading to age-dependent reductions in the photosynthetic rate. These findings suggest that the tree’s age has a significant impact on A. indica × M. azedarach gas exchange during juvenile stages, and the photosynthetic capacity of the hybrid was significantly lower than that of the parental M. azedarach.